(untitled) (Journal of Plant Disease Sciences, 2022)
In the current study, ten isolates of Trichoderma harzianum and T. hamatum collected from different agro climatic zones of Maharashtra were tested for antagonism against important soil borne phytopathogenic fungi (Fusarium ciceri, Rhizoctonia bataticola and Sclerotium rolfsii) using dual culture assay. In comparison to the controls, all T. harzianum isolates had a significant antagonistic effect on pathogen mycelial growth in dual cultures. T. harzianum (AkTr2) inhibited radial mycelial growth by 77.78%, 78.52% and 75.93% in Fusarium ciceri, Rhizoctonia bataticola and Sclerotium rolfsii respectively. Whereas T. hamatum (AkTm1) inhibited 75.93%, 75.56% and 73.70% growth of Fusarium ciceri, Rhizoctonia bataticola and Sclerotium rolfsii respectively. The isolate AkTr2 was the most promising and resulted in the greatest growth inhibition in R. bataticola, while AkTm1 resulted in the least growth inhibition in Sclerotium rolfsii (73.70 %).